2019
DOI: 10.1177/2192568219883256
|View full text |Cite
|
Sign up to set email alerts
|

Structural Allograft Versus PEEK Implants in Anterior Cervical Discectomy and Fusion: A Systematic Review

Abstract: Study Design: Systematic literature review. Objective: Our primary objective was to compare reported fusion rates after anterior cervical discectomy and fusion (ACDF) using structural allograft versus polyetheretherketone (PEEK) interbody devices in patients with cervical spine degeneration. Our secondary objectives were to compare differences in rates of subsidence and reoperation and in patient-reported outcomes between the 2 groups. Methods: Through a systematic review of the English-language literature usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
(148 reference statements)
0
19
0
Order By: Relevance
“…23,24 The large differences in costs of Allo versus SC may drive the primary findings from our analysis. Prior literature has demonstrated that clinical outcomes and postoperative complications are relatively similar between Allo and SC, 13,[25][26][27][28] and SC has slightly higher rates of revision and pseudoarthrosis. 13,25,29,30 Our results highlight that while SC is widely used, it is costineffective with higher monetary costs without providing additional benefit.…”
Section: Discussionmentioning
confidence: 90%
“…23,24 The large differences in costs of Allo versus SC may drive the primary findings from our analysis. Prior literature has demonstrated that clinical outcomes and postoperative complications are relatively similar between Allo and SC, 13,[25][26][27][28] and SC has slightly higher rates of revision and pseudoarthrosis. 13,25,29,30 Our results highlight that while SC is widely used, it is costineffective with higher monetary costs without providing additional benefit.…”
Section: Discussionmentioning
confidence: 90%
“…Because of PEEK high melting point, laser sintering is commonly used, and the mechanical properties, biocompatibility, and heat resistance of PEEK can be effectively improved by adding in other inorganic materials and polymers ( Tan et al, 2005 ). It is reported that the fusion rate of PEEK interbody devices is similar to that of allogeneic bone grafts ( Jain et al, 2020 ).…”
Section: Interbody Fusion Cage Materialsmentioning
confidence: 96%
“…The plate and four screw construct provided a solid fixation for arthrodesis to occur. With fusion rates of up to 100% [19], this technique became the gold standard for 20+ years. While the uniplate had some early adopters [20], high pseudofusion rates were reported [21].…”
Section: Introductionmentioning
confidence: 99%